Comparing Fictional War Hero, Paul Baumr, and US Marine, Sam Siata: A Trauma Study of PTSD Victims in Soldiers - Abbas, Mazhar; Kharal, Ali Ahmad; Shahzadi, Kiran (Pakistan Journal of Humanities and Social Sciences, 2023)
This research focuses on new PTSD symptoms highlighted in C. J. Chiver's case study in "The Fighter" published in the New York Times under the trauma theoretical perspective with the aim to interpret the same in the character of Paul Baumer, the fictional war hero of All Quiet on the Western Front by Eric Maria Remarque. The research first defines PTSD in modern psychiatric terms and reviews it in light of the psychiatric theoretical studies outlined by Miriam Reisman and the trauma theorized by Dominick LaCarpa and Judith Herman. Reviewing the relevant literature to form a theoretical framework for the analysis of PTSD in Baumer, the research seeks to prove that Baumer suffers from PTSD signs. The research finds that Baumer is a soldier tougher than Siam Siatta, the US marine, who suffered the same during his Afghanistan tour. The research also highlights Baumer's peaceful death as compared to Sam Siatta's pulverization of the social fabric to highlight its significance as well as demonstrate ways to cope with such war victims.